Dynamics of competition for resources in Drosophila suzukii (Diptera: Drosophilidae), Zaprionus indianus (Diptera: Drosophilidae) and entomopathogenic fungi - Mendonça, Larine de Paiva (2024)
The arrival of invasive pests in recent years has been facilitated due to advances in globalization. Species are considered invasive when individuals arrive and remain in a new location different from their original location. Therefore, Drosophila suzukii and Zaprionus indianus are considered invasive pests that recently arrived in Brazil. Both D. suzukii and Z. indianus are polyphagous pests. Therefore, they use different fruits as a food source, thus having several substrates in common. By sharing food and space for the development of their individuals, the species are subjected to different types of interaction, such as competitive interaction. Competition is a natural process that can occur in different ways, such as intraspecific, interspecific, and apparent competition. Intraspecific competition involves individuals of the same species exploiting the same resources. Interspecific competition occurs between individuals of different species, and apparent competition is an indirect interaction between individuals sharing a common natural enemy. In this way, we investigated the effects of different competitive interactions between invasive species and their effect on biological and behavioral parameters and their effect on the control of these pests. Firstly, we confirmed the co-occurrence of invasive species in the field. In laboratory tests, we explored the effect of intra and interspecific competition on development, reproduction, behavior, and projection of this interaction over time. D. suzukii, a primary pest, was not affected by the presence of its competitor while Z. indianus showed high reproductive rates when in the presence of D. suzukii, reflecting the densities found in the field. The effect of intraspecific density on the biological control due the indirect interaction of endophytic entomopathogenic fungi in strawberry crops was also explored. The interaction was investigated for pests from different parts of the plant (foliar parts and fruit parts) in two strawberry cultivars (Camarosa and San Andreas) treated with two different entomopathogenic fungi (Beauveria bassiana and Metarhizium robertsii). The control capacity proved to be dependent on the cultivar and pest density since overcompensation was observed for treatments involving the combination of two stresses: fungal inoculation and high density. This shows that control efficiency depends on monitoring pest densities in the field, the cultivar used and the frequency of inoculation processes that must be carried out to guarantee the control capacity of this technique. Finally, the existence of apparent competition between the co-occurring pests D. suzukii and Z. indianus sharing the natural enemy Metarhizium spp was assessed. Although direct interactions between the fungus and individual pests have shown promise for control, it has not been possible to observe strong evidence of apparent competition occurring when pests are interacting with the natural enemy. The results highlight the importance of studying competitive interactions to better understand the pest development and to evaluate the best ways to control them.